ANALISIS KESALAHAN BERBAHASA NETIZEN PADA KOLOM KOMENTAR TIKTOK - Nilam Suryaning Pungkasari; Nova Elisa; Laila Tri Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and explain various forms of linguistic errors found in TikTok comment sections. Employing a qualitative descriptive method, the research examines comments posted by netizens on the platform. Data were collected using